Bandgap voltage reference with low susceptibility to electromagnetic interference (EMI) - De Souza, Flávio Queiroz [UNESP]; Oki, Nobuo [UNESP] (Association for Computing Machinery (ACM), 2011)
In this paper, the susceptibility of a current-mode bandgap voltage reference to electromagnetic interference (EMI) superimposed to the power supply is investigated by simulation. Designed for AMS 0.35 CMOS process, the circuit provides a stable voltage reference in the temperature range of -40-150°C. When EMI disturbances are present, the circuit exhibits only 6.7 mV of offset for interfering signals in the frequency range of 150 kHz-1 GHz. © 2011 ACM.
Keywords: bandgap; current-mode voltage reference.; electromagnetic interference; emi; susceptibility; voltage reference; 0.35 CMOS; Bandgap voltage reference; Current mode; Frequency ranges; Interfering signals; Power supply; Temperature range; CMOS integrated circuits; Electromagnetic pulse; Electromagnetic wave interference; Electromagnetism; Energy gap; Integrated circuits; Signal interference; Systems analysis; Voltage measurement